Kierkegaard, Literature, and the Arts - Ziolkowski, Eric, 1958- (Book collections on Project MUSE., 2018)
Soren Kierkegaard was as much aesthete as philosopher, and his writings are as much literary and music criticism as philosophy. Kierkegaard, Literature, and the Arts contains fourteen essays that focus on the influence and reception of Kierkegaard in literature, the visual arts, and music. The essays in part I focus on Kierkegaard in relationship to literature, his own main medium of expression; part II, to the performing arts, including theater, music, and dance; part III, to visual arts and film; while the essays of part IV are comparative in nature, considering Kierkegaard in juxtaposition with a Romantic poet, a modern composer, and a contemporary musician, singer, and song-writer.